The Economics of Missionary Expansion: Evidence from Africa and Implications for Development - Rémi Jedwab; Felix Meier zu Selhausen; Alexander Moradi (African Economic History Network (AEHN), 2019)
How did Christianity expand in sub-Saharan Africa to become the continent's dominant religion? Using annual panel data on all Christian missions from 1751 to 1932 in Ghana, as well as cross-sectional data on missions for 43 sub-Saharan African countries in 1900 and 1924, we shed light on the spatial dynamics and determinants of this religious diffusion process. Missions expanded into healthier, safer, more accessible, and more developed areas, privileging these locations first. Results are confirmed for selected factors using various identification strategies. This pattern has implications for extensive literature using missions established during colonial times as a source of variation to study the long-term economic effects of religion, human capital and culture. Our results provide a less favorable account of the impact of Christian missions on modern African economic development. We also highlight the risks of omission and endogenous measurement error biases when using historical data and events for identification.
Keywords: N30; N37; N95; O12; O15; Z12; 330; Economics of Religion; Religious Diffusion; Path Dependence; Economic Development; Compression of History; Measurement; Christianity; Africa